Efeitos do aparelho de protrusão mandibular FLF na face: análise pelo método de Farkas modificado - Gonçalves, Ana Lurdes Conte Acunha (2013)
This study aimed to determine the effects of device protrusion FLF associated with fixed orthodontic appliances on the face, through the method of Farkas. The sample consisted of 60 photographs in lateral (30 photos initials and 30 finals photographs) of 30 Brazilian youth (17males and13 female), with an average starting age of 12years and 7 months. Participated in this sample patients caucasian, with Class II malocclusion, 1st division (minimum ½classII), mandibular deficiency and convex profile, complete and permanent dentition pattern balanced growth. The average time of use FLF was 8 months and the total time of treatment with braces and APM FLF was 2 years and one month. To comparison between the sample and the standard FLF Farkas, as well as the comparison between the phases Pre and Posttest was used "t" test and a significance level of 5% (p <0.05). Statistically significant difference between the values of the sample (APM FLF) and sample at T1 Farkas analyzed separately in T2 also analyzed in isolation, but to verify the differenceT2-T1, that is what really happened to the proportion of the face there was no statistically significant difference. Based on this, one can say that the APM FLF no demonstrated impact on the face despite being an effective method for correction of Class II malocclusion